Role of Metabolism in Hepatic Stellate Cell Activation and Fibrogenesis - Hou, Wei; Syn, Wing-Kin (Frontiers in Cell and Developmental Biology, 2018)
Activation of hepatic stellate cell (HSC) involves the transition from a quiescent to a proliferative, migratory and fibrogenic phenotype (i.e. myofibroblast), which is characteristic of liver fibrogeneis. Multiple cellular and molecular signals which contribute to HSC activation have been identified. This review specially focuses on the metabolic changes which impact on HSC activation and fibrogenesis.